2022
DOI: 10.1093/inthealth/ihab070
|View full text |Cite
|
Sign up to set email alerts
|

Vision impairment and self-reported anxiety and depression in older adults in Nigeria: evidence from a cross-sectional survey in Kogi State

Abstract: Background More than 2 billion people are thought to be living with some form of vision impairment worldwide. Yet relatively little is known about the wider impacts of vision loss on individual health and well-being, particularly in low- and middle-income countries (LMICs). This study estimated the associations between all-cause vision impairment and self-reported symptoms of anxiety and depression among older adults in Kogi State, Nigeria. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…Demmin & Silverstein (2020) found an association between visual impairment and anxiety disorder. A study by Gascoyne et al (2022) in Kogi State, Nigeria, reported that severe visual impairment was more associated with anxiety disorder. Similarly, Assi et al (2021) found that worse visual impairment was linked to lower quality of life.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Demmin & Silverstein (2020) found an association between visual impairment and anxiety disorder. A study by Gascoyne et al (2022) in Kogi State, Nigeria, reported that severe visual impairment was more associated with anxiety disorder. Similarly, Assi et al (2021) found that worse visual impairment was linked to lower quality of life.…”
Section: Discussionmentioning
confidence: 97%
“…van der Aa et al (2015) discovered a prevalence of 7.5% among visually impaired older adults using the Diagnostic and Statistical Manual of Mental Disorders IV (DSM-IV) criteria. A study conducted by Gascoyne et al (2022) in Nigeria reported that the prevalences of anxiety among male older adults were 12.7% and 12.4% among females. Another study, also conducted in Nigeria and employed the same instrument, found that the prevalences of anxiety among male and female participants aged 18 years and older with glaucoma and cataract were 35.5% and 21.8%, respectively (Okudo et al 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found no patterns of inequality or significant differences between quintiles for any of our selected eye health outcomes by relative objective asset wealth. Similarly, a 2020 RAAB survey in rural Nigeria included an EquityTool questionnaire benchmarked to 2013 national DHS data 30. The proportion of participants in each quintile was not reported, but there was no pattern of inequality or significant differences in blindness, severe VI or moderate VI across wealth quintiles.…”
Section: Discussionmentioning
confidence: 99%
“…Disability (reported elsewhere 14 ) was measured using the Washington Group Short Set (WGSS) on Functioning a tool comprising six questions regarding self-reported difficulties in six domains of functioning: seeing, hearing, climbing stairs or walking, remembering or concentrating, self-care, and communication 15 . The severity of disability was measured on a graded scale - ‘no difficulty’, ‘some difficulty’, ‘a lot of difficulty’ and ‘cannot do at all’.…”
Section: Methodsmentioning
confidence: 99%